Starting Fever and Its Relationship with 50m Freestyle Swimming in Youth - Othman Mehjoob Khalaf; Mustaf Selah-Al Deen Aziz (College of Physical Education and Sport Sciences, 2020)
The research aimed at identifying the relationship between starting fever and 50m freestyle achievement in youth swimmers by measuring this type of anxiety as a psychological variable and its relationship with achievement as a physical variable. The researchers used the descriptive method on (10) swimmers from Baghdad clubs while the pilot study was conducted on (4) swimmers. They used a starting fever scale in the form of a questionnaire presented to the subjects before an hour from the race. The data was collected and treated using proper statistical operations to conclude a relationship between start fever and 50m freestyle achievement in youth swimmers. Finally, the researchers recommended paying more attention to start fever due to its great importance in 50m freestyle achievement as well as making similar studies on other activities that require speed performance and achievement of swimmers.